Loving‐Kindness Meditation: Systematic Review of Neuroimaging Correlates in Long‐Term Practitioners and Clinical Implications - Kiren Bashir; Stephen B. Edstrom; Sara J. Barlow; Danielle Gainer; Jeffrey D. Lewis (Brain and Behavior)
ABSTRACT Introduction Loving‐kindness meditation (LKM), a meditation type focused on nurturing love and compassion for oneself and others, has been shown to provide mental health benefits, and LKM interventions are being investigated for mental disorders. The benefits of long‐term practice, such as increased self‐compassion, greater cognitive and affective empathy, and prosocial behavior, are proposed to be due to neuroplastic changes that support well‐being. This systematic review aims to summarize the differences in brain structure and function in long‐term practitioners (LTPs) of LKM versus controls to identify possible underlying mechanisms that support mental health and drive treatment effect. Methods The literature search included Google Scholar, PubMed, and APA PsycINFO from inception through November 13, 2023. Results After review, five studies (64 LTPs and 67 controls total) were included. Brain regions with between‐group differences reported in at least two studies include the superior parietal lobe, inferior frontal gyrus, medial frontal lobe, and insular cortex. Conclusion These areas are responsible for self‐compassion, cognitive and affective empathy, and prosociality—personal qualities believed to be fostered through LKM practice. Longitudinal neuroimaging and neurophysiological studies incorporating LKM interventions for specific mental disorders are needed to further inform the biological basis of these treatments and may provide surrogate outcome measures for future clinical trials to refine this promising treatment modality.